Televisão, frustração e agressão: um estudo de caso - Macedo, Pureza Vauthier de (1984)
The objective of the following research was to study the effects of frustration as an instigator of aggression in children behavior. Two groups of children were selected, one experimental group and other control group, in two teaching institutions in the city of Rio de Janeiro. The sample of children under study varied between five to seven years of age. Two films were projected: to the experimental group, one action-adventure film during which frustration was manipulated, and the other - group of control - a neutral film about animal life. The frustration manipulation was introduced by three interruption during the film These interruption were intented to be similar to commercials programs for children. The instruments used were questionnaries answered by teachers and by the children: these questionaries were handled by research assistants. The behavior of the children was video-taped,during the recreation session. The date analyses showed a greater aggression in the group under stimulus of an action-adveture film under frustration. Teoretical considerations were made to the hypothesis whether aggressive behavior is hereditary (instinctive) or conditioned by the environement. It is proposed that behavior does not come from genetical equipement; where the decisions compete to the 'great parliament of the. instincts,' neither comes from social conditioning. The position assumed by the Yale group is criticized while it explains the behavior as an answered to the environement. The influence of cognitive processis in human behavior is assumed. A critique to infantile program of TV is whether it enlarges and diffuses the report of violent stories, or whether these stories are what is educationaly better and whether it is what the infantile audience desires. The infantile programs of TV are in its majority imported from a different culture, strange to our national reality.